2009
DOI: 10.1128/aem.01852-09
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Dynamics of Salmonella Contamination along the Coast of Agadir, Morocco

Abstract: The occurrence of Salmonella enterica in the environment of tropical and desert regions has remained largely uninvestigated in many areas of the world, including Africa. In the present study, we investigated the presence of Salmonella spp. along 122 km of the coastline of Agadir (southern Morocco) in relation to environmental parameters. A total of 801 samples of seawater (243), marine sediment (279), and mussels (279) were collected from six sites between July 2004 and May 2008. The overall prevalence of Salm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 36 publications
5
36
2
Order By: Relevance
“…in Morocco [3] , in Spain [4] , in Vietnam [5] , in India [6] ; L. monocytogenes in Spain [7] , in USA [8] , in India [9] , in Denmark [10] , in Iran [11] . In Turkey the prevalence of these pathogens has not been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…in Morocco [3] , in Spain [4] , in Vietnam [5] , in India [6] ; L. monocytogenes in Spain [7] , in USA [8] , in India [9] , in Denmark [10] , in Iran [11] . In Turkey the prevalence of these pathogens has not been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…These activities disseminate Salmonella causing gastroenteritis and typhoid in the district (Attua et al, 2015). Not all Salmonellae serotypes found in the environments are the same as those isolated from humans (Setti et al, 2009) because some isolates are associated with animals (Levantes et al, 2012;Andoh et al, 2016). In this present study well water samples yielded Salmonella serovars commonly associated with human clinical disease (Abdulkadir et al, 2014).…”
Section: Discussionmentioning
confidence: 70%
“…In other studies from Spain, Morocco and Mexico, the proportion of seawater samples positive for Salmonella spp. varied from 2.3 to 4.1 % (Martinez- Urtaza et al, 2004;Setti et al, 2009;Simental and Martinez-Urtaza, 2008). Efstratiou et al (2009) showed that levels of either total coliforms or faecal coliforms adequately predicted the likelihood of the presence of Salmonella in seawater samples, although enterococci did not.…”
Section: Salmonellamentioning
confidence: 99%